Considering multiple governance levels in epidemiologic analysis of public policies. (December 2022) - Schnake-Mahl, Alina S.; Jahn, Jaquelyn L.; Purtle, Jonathan; Bilal, Usama
Abstract: Epidemiology is increasingly asking questions about the use of policies to address structural inequities and intervene on health disparities and public health challenges. However, there has been limited explicit consideration of governance structures in the design of epidemiologic policy analysis. To advance empirical and theoretical inquiry in this space, we propose a model of governance analysis in which public health researchers consider at what level 1) decision-making authority for policy sits, 2) policy is implemented, 3) and accountability for policy effects appear. We follow with examples of how these considerations might improve the evaluation of the policy drivers of population health. Consideration and integration of multiple levels of governance, as well as interactions between levels, can help epidemiologists design studies including new opportunities for quasi-experimental designs and stronger counterfactuals, better quantify the policy drivers of inequities, and aid research evidence and policy development work in targeting multiple levels of governance, ultimately supporting evidence-based policy making.